Design and analysis of an impact energy absorbing steering system. (2018) - Patil, M.S.; Galgali, Varun
In a country that continues to hold the record for high road deaths every year, it is important to have reliable safety system in vehicles which is an absolutely crucial pre-requisite for driver safety. The latest tests, conducted by Global NCAP (New Car Assessment Program), showed that in an accident, most budget cars would leave the driver with possible life-threatening injuries. For such cars with insufficient or unreliable safety devices, this paper deals with the design of an impact absorbing steering column, used to achieve controlled deceleration of a restrained/unrestrained occupant to reduce the impact forces and thus reducing the chances of fatal injuries.